Development of a Herbal Fairness Cream - Wimalasekara, H.N.; Paranagama, P.A.; Herapathdeniya, S.K.M.K. (Faculty of Indigenous Medicine, University of Colombo, 2021)
There are reports in the public domain which state that artificially ...
Keywords: antibacterial; antioxidant; fairness cream